Cell Curvature and Far-Field Superconvergence in Numerical Solutions of Electromagnetic Integral Equations - Andrew F. Peterson (International Journal of Antennas and Propagation)
Two curved targets are used to explore far-field superconvergence effects arising in numerical solutions of the electric-field and magnetic-field integral equations. Three different orders of basis and testing functions are used to discretize these equations, and three different types of target models (flat facets, quadratic-curved facets, and cubic-curved facets) are employed. Ideal far-field convergence rates are only observed when the model curvature is one degree higher than the basis order.